2004
DOI: 10.1074/mcp.m400004-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteomics Reveals Multiple Components in Retrogradely Transported Axoplasm After Nerve Injury

Abstract: Information on axonal damage is conveyed to neuronal cell bodies by a number of signaling modalities, including the post-translational modification of axoplasmic proteins. Retrograde transport of a subset of such proteins is thought to induce or enhance a regenerative response in the cell body. Here we report the use of a differential 2D-PAGE approach to identify injury-correlated retrogradely transported proteins in nerves of the mollusk Lymnaea. A comprehensive series of gels at different pI ranges allowed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Forty proteins that were retrogradely transported have been identified by two-dimensional PAGE and mass spectrometry in regenerating axons of the snail Lymnea stagnalis. Several of them comprise posttranslationally modified proteins and calpain cleavage products of a 51-kDa intermediate filament protein (254,255). Similar analyses made on purified axons of injury-conditioned dorsal root ganglion neurons led to the identification of cytoskeletal proteins and a large number of other proteins, including heat shock proteins, endoplasmic reticulum proteins, enzymes, and proteins associated with neurodegenerative diseases (330).…”
Section: Vertebrate Axonsmentioning
confidence: 82%
See 1 more Smart Citation
“…Forty proteins that were retrogradely transported have been identified by two-dimensional PAGE and mass spectrometry in regenerating axons of the snail Lymnea stagnalis. Several of them comprise posttranslationally modified proteins and calpain cleavage products of a 51-kDa intermediate filament protein (254,255). Similar analyses made on purified axons of injury-conditioned dorsal root ganglion neurons led to the identification of cytoskeletal proteins and a large number of other proteins, including heat shock proteins, endoplasmic reticulum proteins, enzymes, and proteins associated with neurodegenerative diseases (330).…”
Section: Vertebrate Axonsmentioning
confidence: 82%
“…) end of the proximal stump of axotomized neurons (174,177) demonstrates the participation of local protein synthesis in axon regeneration. Its physiological significance has been recently elucidated by investigations of regenerating axons in various model systems (75,101,133,134,146,215,254,255,302,330,339; for reviews, see Refs. 23,331).…”
Section: B Nerve Terminalsmentioning
confidence: 99%
“…Nerve injury studies must also contend with variations in inflammatory and other responses in injured versus non-injured tissues. Previous studies of axonally transported complexes using proteomics used either affinitytargeted investigations of purified organelles (28 -30) or gel-based differential screens (15,31). Here, we sought to obtain a more comprehensive view of axon transport ensemble changes induced by nerve injury by interrogating ligature axoplasm preparations with iTRAQ quantification and LC-MS/ MS.…”
Section: Fig 3 Pca Analysis For Itraq Datamentioning
confidence: 99%
“…This prominent role for post-transcriptional processes suggests that comprehensive characterization of retrograde signaling will require proteomics approaches. In a previous study we used two-dimensional PAGE and mass spectrometry to analyze retrogradely concentrated axoplasm from injured mollusc nerve, identifying a vesicular ensemble blocked by the lesion and an up-regulated ensemble highly enriched in calpain cleavage products of an intermediate filament (14,15). Follow-up studies in rodent sciatic nerve showed that the mammalian intermediate filament vimentin is produced by local translation of axonal mRNA upon axonal injury and then undergoes calpain-mediated proteolysis, generating a cleavage product that interacts with importins bound to dynein and enables protected retrograde transport of phosphorylated forms of the mitogen-activated protein kinases Erk1 and Erk2 (16,17).…”
mentioning
confidence: 99%
“…However, other proteins that might be carried by importin-dynein complexes were not identified in those investigations. Retrograde transport of ~30 proteins was demonstrated in cultured frog nerves by Edbladh et al (Edbladh et al, 1994), and of >100 proteins in lesioned nerves of the mollusc Lymnia (Perlson et al, 2004), although the identities and possible roles of those proteins in axonal regeneration are largely unknown.…”
Section: Retrograde Signallingmentioning
confidence: 99%